Protest by Potchefstroom native location's residents against dominance, 1904 to 1950 (Historia, 2021)
This article indicates the importance of a thorough study of local sources on protest action by township residents in Makweteng (earlier known as Potchefstroom's native location) against oppressive laws and policies in South Africa. Although the term 'grassroots support' only became a common one much later in South Africa's history, the study of local documents indicates the protracted broad swell of dissatisfaction among black South African citizens against legalised segregation and later apartheid. In the case of some individuals and local organisations these views articulated with protests on a national level.This article covers the period 1904 to 1950 and looks at the strenuous efforts by white authorities to dominate this township on a municipal level; the limited influence of the native advisory bodies and localised national organisations in resisting this control; and the singular abilities and contributions of Lazarus R. Muthle and James Z. Mdatyulwa in Potchefstroom's protests. It also indicates how this protest gradually helped to build the basis for encompassing resistance, including resistance of an intellectual nature, in the 1970s and 1980s. Hierdie artikel dui op die belang van 'n grondige studie van plaaslike bronne in verband met protes en weerstand van 'n township (vroeër, Potchefstroomse naturelle-lokasie) se inwoners teen onderdrukkende wetgewing en behandeling in Suid-Afrika. Alhoewel die term "grassroots support" (voetsoolvlak-steun) eers heelwat later in die Suid-Afrikaanse geskiedenis 'n algemene term geword het; dui die studie van plaaslike dokumente op die uitgerekte en wye golf van ontevredenheid onder swart Suid-Afrikaanse burgers teen wetlike segregasie en later apartheid; en hoe, in die geval van sekere individue en plaaslike organisasies, hierdie sienings geartikuleer het met protes op nasionale vlak. Die artikel dek die enorme pogings van die wit munisipale owerhede om die lokasie te domineer, die uiters beperkte invloed van die naturelle-adviesrade en ook gelokaliseerde nasionale organisasies om hierdie beheer te weerstaan, die uitsonderlike vermoëns en bydraes van Lazarus R. Muthle en James Z. Mdatyulwa in Potchefstroomse protes en hoe, deur hulle optrede op plaaslike vlak, en te midde van hul wisselvallige verblyfreg, hierdie protes geleidelik bygedra het tot die onderbou van omvattende weerstand, insluitende dié van 'n intellektuele aard in die 1970s en 1980s.
Keywords: Advisory board; Native Location; Potchefstroom; Protes; Protest; Adviesraad; Apartheid; Muthle; Mdatyulwa; Naturelle-lokasie